WHAT DRIVES MICROFINANCE CREDIT DISBURSEMENT? AN EMPIRICAL EVIDENCE FROM INDONESIA’S RURAL BANKS (BPRs) - Pranata, Nika; Nurzanah, Nurzanah (Pusat Penelitian Ekonomi-LIPI, 2017)
The paper investigates determinants of Indonesia’s microfinance credit disbursement, case taken from Indonesia’s rural banks (BPRs) which primarily focus on providing funding to the Micro and Small Enterprises (MSEs). The study applies Autoregressive Distributed Lag (ARDL) model by using monthly data over the period of January 2009 to January 2016. Result indicates that rural banks credit disbursement is more determined by demand side rather than supply side as variable representing demand side (production index) has significant effect to credit disbursement both long run and short run. In terms of supply side, the amount of credit disbursement is affected by interbank fund in the long run, whereas in the short run the significant variables are customer fund and internal fund. In addition, Consumer Price Index (CPI) and Non-Performing Loan (NPL) impose significant effect to the microfinance credit disbursement; yet, interestingly, interest rate is not a significant factor in microfinance’s case.